Sentiment Analysis of Product Reviews in the Sales System of Putra Electronics Store - Wulandari, Maria Sri; Noveandini, Rahayu; Chandra, Yudi Irawan; Putra, Noval Dwi (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The Putra Elektronik Store is a commercial establishment that sells various electronic goods, including mobile phones, desktop computers, and laptops, among other products. The procedure for conducting transactions, which has been ongoing until now, is still done manually. The author suggests developing an online sales platform based on this information. The system design uses UML in addition to the programming languages PHP and Laravel. In addition, a tool for collecting customer reviews has also been developed. The purpose of this feature is to determine whether consumers' feelings regarding the things being offered are favorable or unfavorable by employing the navel Bayes algorithm and weighting tf (term frequency) and probability..